New species of Hybos Meigen from Guangdong Province, South China (Diptera: Empididae) - Yang, Ding; Gaimari, Stephen D.; Grootaert, Patrick (Zootaxa, 2005)
The following three new species of the genus Hybos Meigen, from Guangdong Province, China, are described as new to science: Hybos mangshanensis, H. nankunshanensis, H. xiaohuangshanensis. Their relationships with related species are discussed.